Highly effective anti-tumor nanomedicines based on HPMA copolymer conjugates with pirarubicin prepared by controlled RAFT polymerization. (1st April 2020) - Randárová, Eva; Nakamura, Hideaki; Islam, Rayhanul; Studenovský, Martin; Mamoru, Haratake; Fang, Jun; Chytil, Petr; Etrych, Tomáš
Abstract: Here, we describe innovative synthesis of well-defined biocompatible N -(2-hydroxypropyl) methacrylamide (HPMA)-based polymer carriers and their drug conjugates with pirarubicin intended for controlled drug delivery and pH-triggered drug activation in tumor tissue. Polymer carrier synthesis was optimized to obtain well-defined linear HPMA-based polymer precursor with dispersity close to 1 and molar mass close to renal threshold with minimal synthesis steps. The developed synthesis enables preparation of tailored polymer nanomedicines with highly enhanced biological behavior in vivo, especially the biodistribution, urine elimination, tumor accumulation and anticancer activity. Statement of Significance: The manuscript reports on novel synthesis and detailed physicochemical characterization and in vivo evaluation of well-defined biocompatible hydrophilic copolymers based on N -(2-hydroxypropyl)methacrylamide (HPMA) and their drug conjugates with pirarubicin enabling controlled drug delivery and pH-triggered drug activation in tumor tissue. Polymer carrier synthesis was optimized to obtain well-defined linear HPMA-based polymer precursor with minimal synthesis steps using controlled polymerization. Compared to previously published HPMA-based polymer drug conjugates whose polymer carriers were prepared by classical route via free radical polymerization, the newly prepared polymer drug conjugates exhibited enhanced biological behavior in vivo, especially the prolonged blood circulation, urine elimination, tumor accumulation and excellent anticancer activity. We believe that the newly prepared well-defined polymer conjugates could significantly enhance tumor therapy in humans. Graphical abstract: Image, graphical abstract